ECONOMIC IMPORTANCE AND CURATIVE PROPERTIES OF CHICORY - O. M. Vjutnova; I. A. Novikova (Овощи России, 2018)
The economic importance of chicory root as raw material for the food industry and for other sectors of the economy is presented in the article. Healing properties of the culture and its application in the medical purposes have been also shown.